ANALISIS PERBANDINGAN SEBELUM DAN SESUDAH PANDEMI COVID–19 TERHADAP KINERJA KEUANGAN PERBANKAN (Studi Empiris pada PT Bank Negara Indonesia Persero Tbk) - Rizky Apriluviar; Cecep Hermana (Sekolah Tinggi Ilmu Ekonomi Dewantara, 2024)
This research aims to analyze the comparison before and after the Covid-19 pandemic on banking financial performance, particularly at PT Bank Negara Indonesia Persero Tbk, to evaluate RGEC (Risk Profile, Governance, Earnings, and Capital) as assessment indicators. This research uses a quantitative analysis method on PT Bank Negara Indonesia Persero Tbk's financial reports, with data sourced from the 2019-2023 Annual Report of PT Bank Negara Indonesia Persero Tbk. The research results show that before and after the Covid-19 pandemic, in the Risk Profile analysis, the NPL in 2020 was 4.3%, categorized as Healthy credit. The LDR in 2019 was 91.5%, categorized as Fairly Healthy credit. In the Governance analysis, KI in 2023 was criticized as a Very Low credit with a rate of 2.68%. Meanwhile, the PDKI in 2019, 2021, and 2022 maintained the same value of 1.75%. In the Earnings analysis, the NIM consistently obtained a value of 4, indicating that the company's income condition faces quite a significant problem. The BOPO reached its highest value in 2020 at 93.3%, indicating that income is not yet efficient. In the Capital analysis, the CAR in 2020 experienced a very low value compared to other years, with a rate of 15.7%.